Efektivitas kapasitas kerja dalam pengelolaan lanskap area permainan Emeralda Golf Club, Tapos, Depok - Muplihudin, Muplihudin; Putra, Priambudi Trie; Syahadat, Ray March; Radnawati, Daisy (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019DO - 10.24843/JAL.2019.v05.i01.p12, 2019)
Working Capacity Effectivity in Landscape Management of Game Area at Emeralda Golf Club, Tapos, Depok. Golf course landscape are one of the green open space form that created for recreational sports. Inside the golf course is dominated by grass. One of the golf courses in Depok is Emeralda Golf Club. So far at Emeralda Golf Club, there has never been a study on working capacity. As a result, there has no definite reports on management and number of workers. The aims of this study was to calculate the effectiveness of working capacity in the Emeralda Golf Club. Study was limited at the game area at Emeralda Golf Course. The stages were preparation, data collection, analysis, and synthesis. Data collected by observation, interviews, and literature studies. The data analyzed both qualitatively and quantitatively. The results obtained by the number of workers are still considered not enough to meet the standards in managing the golf course.